Asy-Syakhshiyatu Al-Sardiyatu Wa Tamtsilatuha Fi Thali’ati Kutubi al-Adabi al-Abbasi (االشخصيات السردية وتمثلاتها في طليعة كتب العصر العباسي الأول ( نماذج ومختارات ) - Elsayed Mohamed Salem, Salem Elawadi (2020)
Literature of its two kinds reached, during the Abbasid era, to the peak of goodness and splendor, whereby the mingling of Arabs with non-Arabs had its far-reaching impacts in refining the ideas and imagination, the maturity of culture, and improving the types of speech; poetry and prose. The narrative discourse took its best chance when the literary arts diversified in that era, and the narration should not be without a time in which events are narrated and characters revolve in its orbit. Hence this study came to shed light on narrative characters because it is the column of narrative narrative construction, and to show the types of narrative characters, and follow these different types of characters in samples from the early books of narration, such as "Fun and Familiarity”, “The Animal”, “The Statement and Clarification”, the “Calella and Damnah” and “Women's News”, using the descriptive and the analytical approaches, and thus To explore his gore and to discover its essence.